Analisis Pengaruh Net Profit Margin (NPM), Return on Investment (ROI) dan Total Asset Turn Over (TATO) terhadap Pertumbuhan Laba pada PT. Semen Indonesia, Tbk. - Sri Dewi Nurkomalasyari; Ita Purnama (Universitas Bumigora, 2022)
This study aims to examine and analyze the effect of net profit margin, return on investment and total asset turnover on profit growth at Indonesian cement companies listed on the Indonesian stock exchange in 2006-2020. The data used in this study is secondary data obtained from the financial reports of Indonesian cement companies listed on the Indonesian stock exchange. The analytical method used in this research is multiple linear regression analysis. The sample in this study was 15 years old with a purposive sampling technique as the sampling method. The results of this study indicate that the net profit margin variable has a significant effect on profit growth, return on investment has a significant negative effect on profit growth and total asset turnover has a significant effect on profit growth.